ANALYSIS OF EFFECTIVENESS AND EFFICIENCY OF EXPENDITURE BUDGET ABSORPTION AT UNIVERSITAS NEGERI MALANG FOR THE 2019-2021 FISCAL YEAR - Djuni Farhan; Puji Agus Kurniawan (International Journal of Economics and Management Research, 2023)
Financial governance in the management of the expenditure budget is a planning tool to indicate targets to be achieved and a control tool to indicate the allocation of funds. The budget that has been set can be used as a standard for performance measurement activities, so every organization is expected in controlling or supervising to pay attention to and improve performance with value for money, namely effectively and efficiently. This study aims to analyze: (1) measure the effectiveness and efficiency of budget absorption at Universitas Negeri Malang for the 2019-2021 Fiscal Year, (2) analyze the level of effectiveness and efficiency of budget absorption at Malang State University for the 2019-2021 Fiscal Year The research method used is descriptive qualitative with a case study research method using non-statistical qualitative research techniques. The results showed that there were expenditure programs that were not realized and several other programs whose realization was not optimal so they did not reach the target.